2017
DOI: 10.7324/jabb.2017.50606
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and curative control of sclerotium rot disease of cocoyam cormel (Colocasia esculenta [L., Scott]) using plant extracts and Trichoderma koningii

Abstract: Aqueous leaf extracts from air-dried samples of Carica papaya, Chromolaena odorata, and Azadirachta indica were screened for antifungal properties against Sclerotium rolfsii at 50, 70, and 100% concentrations and Trichoderma koningii (4.9 × 10 6 spores/ml) in vivo. Dithane M45 at 2% concentration was used as positive control for better comparison. The aqueous extracts and T. koningii were applied as preventive and curative methods by spraying fresh and healthy cormels with S. rolfsii (3.75 × 10 5 spores/ml). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This result indicates that the extracts of the test plants could effectively reduce rot development in Irish potato tubers at test concentrations. The ability of plant extracts to reduce rot in tuber crops have been reported by earlier researchers (Nwachukwu and Osuji, 2008;Strivastava andKshma, 2014: Boungab et al 2015;Nwauzoma et. al., 2017).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This result indicates that the extracts of the test plants could effectively reduce rot development in Irish potato tubers at test concentrations. The ability of plant extracts to reduce rot in tuber crops have been reported by earlier researchers (Nwachukwu and Osuji, 2008;Strivastava andKshma, 2014: Boungab et al 2015;Nwauzoma et. al., 2017).…”
Section: Discussionsupporting
confidence: 59%
“…Similar results on the reduction of weight loss using ashes from the bark of kola nut tree, neem tree, and inflorescence of oil palm have been reported (Eze, 1991). In a related study, Nwauzoma et al (2017) reported that leaf extracts of Carica papaya, Chromolaena odorata and Azadirachta indica significantly reduced rot in Sclerotium rolfsii inoculated tubers after 14 days in storage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation